Olverembatinib (HQP1351)-based therapy in adults with relapsed or refractory Philadelphia chromosome-positive acute lymphoblastic leukemia or chronic myeloid leukemia in blast phase: results from a real-world study - Wen, Ziyu; Liu, Zhi; Ye, Xu; Fan, Zhiping; Lin, Ren; Huang, Fen; Xuan, Li; Li, Xiaofang; Jin, Hua; Dai, Min; Sun, Jing; Zhou, Xuan; et al. (Frontiers in Immunology, 2025)
BackgroundRelapsed or refractory Philadelphia chromosome-positive acute lymphoblastic leukemia (R/R Ph+ ALL) and chronic myeloid leukemia in the blast phase (CML-BP) are associated with poor prognoses. Olverembatinib (HQP1351), a novel third-generation tyrosine kinase inhibitor (TKI), has shown promising efficacy and safety in clinical trials against nearly all BCR-ABL1 kinase mutations, including T315I.MethodsData were collected and analyzed to evaluate the efficacy and safety of olverembatinib-based therapy for advanced Ph+ leukemia. The primary outcome was the overall response rate at 28 days. Secondary outcomes included overall survival (OS), event-free survival (EFS), disease-free survival (DFS), the proportion of patients undergoing allo-HSCT, and adverse events.ResultsA total of 59 patients participated in the study, including 40 patients with Ph+ ALL and 19 with CML-BP. Among them, 36 (61.0%) were men, and 23 (39.0%) were women. The median age was 39 years (interquartile range [IQR], 30–48), and the median follow-up duration was 7.8 months (IQR, 4.1–11.3). A total of 16 (27.1%) and 11 patients (18.6%) had received treatment with two and ≥ 3 prior TKIs, respectively. Additionally, 19 patients (33.9%) had been treated with ponatinib. In a cohort of 19 CML patients, 12 (63.2%) achieved CR/CRi by day 28. Five (26.3%) achieved a complete cytogenetic response with a median duration of 2.9 months, and two (10.5%) achieved a major molecular response with a median duration of 5.5 months. Among 40 evaluated ALL patients, 37 (92.5%) achieved CR/CRi by day 28, 30 (75.0%) attained MRD negativity, and 22 (55.0%) achieved CMR. The probabilities of DFS, EFS, and OS at 12 months were 80.3% (95% confidence interval [CI]: 61.0%–90.7%), 80.2% (95% CI: 61.0%–90.7%), and 93.3% (95% CI: 75.8%–98.3%) for patients with R/R Ph+ ALL, compared to 52.0% (95% CI: 17.7%–78.0%), 23.0% (95%CI, 4.2%-50.6%), and 75.6% (95% CI: 37.7%–92.3%) for those with CML-BP. The prevalent treatment-related nonhematologic adverse events, primarily classified as grade 1/2, included skin hyperpigmentation, proteinuria, increased liver enzyme levels, and hypertriglyceridemia.ConclusionsOlverembatinib-based therapy demonstrated significant efficacy and manageable toxicity in patients with advanced Ph+ leukemia.